Sequence Analysis of a Functional Drosophila Centromere - Sun, Xiaoping; Le, Hiep D.; Wahlstrom, Janice M.; Karpen, Gary H. (Genome Research, 2003)
Centromeres are the site for kinetochore formation and spindle attachment and are embedded in heterochromatin in most eukaryotes. The repeat-rich nature of heterochromatin has hindered obtaining a detailed understanding of the composition and organization of heterochromatic and centromeric DNA sequences. Here, we report the results of extensive sequence analysis of a fully functional centromere present in theDrosophila Dp1187 minichromosome. Approximately 8.4% (31 kb) of the highly repeated satellite DNA (AATAT and TTCTC) was sequenced, representing the largest data set of Drosophilasatellite DNA sequence to date. Sequence analysis revealed that the orientation of the arrays is uniform and that individual repeats within the arrays mostly differ by rare, single-base polymorphisms. The entire complex DNA component of this centromere (69.7 kb) was sequenced and assembled. The 39-kb “complex island” Maupiti contains long stretches of a complex A+T rich repeat interspersed with transposon fragments, and most of these elements are organized as direct repeats. Surprisingly, five single, intact transposons are directly inserted at different locations in the AATAT satellite arrays. We find no evidence for centromere-specific sequences within this centromere, providing further evidence for sequence-independent, epigenetic determination of centromere identity and function in higher eukaryotes. Our results also demonstrate that the sequence composition and organization of large regions of centric heterochromatin can be determined, despite the presence of repeated DNA.[Supplemental material is available online atwww.genome.org. The sequence data from this study have been submitted to GenBank under accession nos.:Beagle = AY183918, F = AY183919,412 = AY183920, Bel = AY183921, You = AY183922, Maupiti = AY183926, AATAT = AY183925, AY183931–AY184007, and TTCTC = AY183923–AY183924, AY183927–AY183930,AY184008–AY184069].